Қ. КАМАЛОВТЫҢ ӨМИРИ ҲӘМ ИЛИМИЙ-КӨРКЕМ ДӨРЕТИЎШИЛИГИ - Алламбергенов, К. (FAN va JAMIYAT, 2019)
The article is devoted to the scientific theoretical analysis of life and creative activity of the famous specialist in literature, critic, scholar and representative of literary criticism and Karakalpak literature of the XX-th century K.Kamalov. In the focus of the author’s attention is the great contribution of the scholar into the study of such genre as a story and the literary-artistic method in Karakalpak literare